National Institute for Pharmaceutical Technology and Education Special Issue - Xiuling Lu; Vadim J. Gurvich; Dale Eric Wurster (Pharmaceutical Research, 2026)

Impact of Mixing Approach and Bubble Formation on In Situ Forming Implant Properties - Xinhao Lin; Seyyed Majid Eslami; Zixuan Zhen; Hong Yuan; Eric Wilson Livingston; Ananya Aggarwal; Mia Atallah; Andre O’Reilly Beringhs; Qi Li; Qiangnan Zhang; Qin Bin; Yan Wang; et al. (Pharmaceutical Research, 2026)

The synergistic effects of co-exposure of water disinfection byproducts DCBQ and DBBQ on lipid metabolism of mice - Ziqiao He; Xue Han; Tianyue Zhang; Yuewen Yang; Minghan Jiang; Xu Zhang; Haiying Du; Rifeng Lu; Xiuling Song; Jinhua Li (Chemico-Biological Interactions, 2026)

Lipid Nanoparticle Development in Practice: Challenges and Collective Insights - Xiuling Lu; Sheyda Ranjbar; Fan Zhang; Yahya Choonara; Ryan M. Pearson; John Fetse; Rui He; Esraa Mohamed; Amalendu Ranjan; Muhammad Delwar Hussain; Ashraf Hatim Osman Mohamed Kheir; Chun-Wan Yen; et al. (Pharmaceutical Research, 2026)

Span80 induced orderly diffusion of monomer for the construction of small pore volume polyamide nanofiltration membrane with high Li/Mg separation ratio - Lu Gao; Yue Miao; Xiaowen Huo; Yingying Zhao; Zhaojing Jing; Xiuling Liu; Haitao Wang; Ning Fan; Qiuying Jia; Kai Ren; Jun Li; Na Chang (Desalination, 2026)

Hydrogel-confined molecular iron catalyst enables enhanced selective photoelectrochemical oxidation of glycerol to glycolaldehyde - Lu Wang; Zizhong Chen; Qi Zhao; Xiuling Jiao; Dairong Chen; Yuguo Xia (Chemical Engineering Journal, 2026)

Physiological Considerations and Delivery Strategies for Targeting Tumors Through Intraperitoneal Delivery - Md Jobair Hossen Jony; Sheyda Ranjbar; Rama Prajapati; Seyyed Majid Eslami; Zixuan Zhen; Mittal Darji; Xueli Zhu; Xiuling Lu (Pharmaceutical Research, 2025)

Thermally triggered surface reconstruction enables self-protective layer for enhanced charge transfer in CdIn2S4 photoelectrode - Zizhong Chen; Lu Wang; Xiuling Jiao; Yuguo Xia; Dairong Chen (Chemical Engineering Journal, 2025)

Defect-mediated spatial confinement of Pt single atoms on photoactive CdIn2S4 octahedrons: Synergistic carrier dynamics optimization for photocatalytic hydrogen production - Zizhong Chen; Lu Wang; Xiuling Jiao; Yuguo Xia; Dairong Chen (Chemical Engineering Journal, 2025)

Rett syndrome: Pathogenicity and regulation of MECP2 (human) and Mecp2 (mouse) genes and their protein products through various molecular mechanisms - Bashir Ahmad; John Sieh Dumbuya; Ji-Xin Tang; Wen Li; Xiuling Chen; Jun Lu (Mutation Research - Reviews in Mutation Research, 2025)

3D printing fortified pea-based snacks with precise vitamin dosing by binder jetting - Ethan Chadwick; Guilherme P.S.R. Bertola; Xinhao Lin; Ann H. Barrett; Michael Okamoto; Xiuling Lu; Anson W.K. Ma (Journal of Food Engineering, 2025)

Configuration of pore structure and related functions in macroaggregates following long-term organic and inorganic fertilization - Xiuling Yu; Xiaomin Zhang; Sibo Zhan; Shenggao Lu (Soil and Tillage Research, 2025)

Geographic variation and pedogenic implications of soil minerals across climatic zones of China quantified by Rietveld method - Xiuling Yu; Xiaomin Zhang; Sibo Zhan; Guanglie Lv; Shenggao Lu (CATENA, 2025)

Accelerating peroxymonosulfate activation over fiber-shaped Fe@Fe3C/CNF for ultrafast tetracyclines degradation: Active site synergy and mechanisms - Man Yang; Yafan Lu; Wenjuan Zhang; Long Xie; Junjie Tian; Yiliyasi Baikeli; Fang Wang; Yong-Zheng Zhang; Da-Shuai Zhang; Xiuling Zhang; Mika Sillanpää; Longlong Geng (Journal of Environmental Chemical Engineering, 2024)

State of the Art of Silica Nanoparticles: An Overview on Biodistribution and Preclinical Toxicity Studies - Joshua Yu; Nirnoy Dan; Seyyed Majid Eslami; Xiuling Lu (The AAPS Journal, 2024)

Accelerating Drug Product Development and Approval: Early Development and Evaluation - Annette Bak; Rubi Burlage; Nigel Greene; Prabu Nambiar; Xiuling Lu; Allen Templeton (Pharmaceutical Research, 2024)

Impact of Apparatus and Adapter on In vitro Drug Release of Ophthalmic Semisolid Drug Products - Catheleeya Mekjaruskul; André O’Reilly Beringhs; Bin Qin; Yan Wang; Pallabita Chowdhury; Xiuling Lu (Pharmaceutical Research, 2023)

Facile one-pot synthesis of multifunctional tetracycline hydrochloride nanoparticles with high stability and photothermal effect for synergistically improved antibacterial performance and sustainability - Mingzhou Lu; Weitao Wang; Xiuling Fang; Yang Xuan; Liying Chen; Xiaojing Wang; Jianhao Wang; Cheng Wang (Sustainable Chemistry and Pharmacy, 2023)

Time-frequency connectedness and cross-quantile dependence between carbon emission trading and commodity markets: Evidence from China - Haozhi Qi; Tiantian Wu; Hao Chen; Xiuling Lu (Resources Policy, 2023)

National Institute for Pharmaceutical Technology & Education (NIPTE) Research and Perspective: Advances in Nanotechnology-Based Drug Delivery - Aliasger K. Salem; Xiuling Lu (AAPS PharmSciTech, 2021)

Stabilization and X-ray Attenuation of PEGylated Cholesterol/Polycaprolactone-Based Perfluorooctyl Bromide Nanocapsules for CT Imaging - André O’Reilly Beringhs; Dennis Ndaya; Reuben Bosire; Rajeswari M. Kasi; Xiuling Lu (AAPS PharmSciTech, 2021)

Applications of Nanoparticle-Antibody Conjugates in Immunoassays and Tumor Imaging - Xinhao Lin; André O’Reilly Beringhs; Xiuling Lu (The AAPS Journal, 2021)
Modern diagnostic technologies rely on both in vitro and in vivo modalities to provide a complete understanding of the clinical state of a patient. Nanoparticle-antibody conjugates have emerged as promising systems to confer increased sensitivity and accuracy for in vitro diagnostics (e.g., immunoassays). Meanwhile, in vivo applications have benefited from the targeting ability of nanoparticle-antibody conjugates, as well as payload flexibility and tailored biodistribution. This review provides an encompassing overview of nanoparticle-antibody conjugates, from chemistry to applications in medical immunoassays and tumor imaging, highlighting the underlying principles and unique features of relevant preclinical applications employing commonly used imaging modalities (e.g., optical/photoacoustics, positron-emission tomography, magnetic resonance imaging, X-ray computed tomography).

Impact of Membranes on In Vitro Release Assessment: a Case Study Using Dexamethasone - Catheleeya Mekjaruskul; André O’Reilly Beringhs; Wei-Chung Luo; Qingguo Xu; Matthew Halquist; Bin Qin; Yan Wang; Xiuling Lu (AAPS PharmSciTech, 2021)

Impact of Porous Excipients on the Manufacturability and Product Performance of Solid Self-Emulsifying Drug Delivery Systems - André O’Reilly Beringhs; Bruna Cristina Minatovicz; Geoff G. Z. Zhang; Bodhisattwa Chaudhuri; Xiuling Lu (AAPS PharmSciTech, 2018)

Influence of Manufacturing Process Variables on the Properties of Ophthalmic Ointments of Tobramycin - Shilpa Patere; Bryan Newman; Yan Wang; Stephanie Choi; Sahil Vora; Anson W. K. Ma; Michael Jay; Xiuling Lu (Pharmaceutical Research, 2018)

Native promoters of Corynebacterium glutamicum and its application in l-lysine production - Xiuling Shang; Xin Chai; Xuemei Lu; Yuan Li; Yun Zhang; Guoqiang Wang; Chen Zhang; Shuwen Liu; Yu Zhang; Jiyin Ma; Tingyi Wen (Biotechnology Letters, 2018)

Upregulation of hydroxysteroid sulfotransferase 2B1b promotes hepatic oval cell proliferation by modulating oxysterol-induced LXR activation in a mouse model of liver injury - Zhengyang Wang; Xiaoming Yang; Liang Chen; Xiuling Zhi; Hanyu Lu; Yanxia Ning; Joe Yeong; Sifeng Chen; Lianhua Yin; Xinhong Wang; Xiaobo Li (Archives of Toxicology, 2017)

Micrometer-scale internal structure and element distribution of Fe-Mn nodules in Quaternary red earth of Eastern China - Xiuling Yu; Shenggao Lu (Journal of Soils and Sediments, 2016)

Characterizing soil pore structure using nitrogen adsorption, mercury intrusion porosimetry, and synchrotron-radiation-based X-ray computed microtomography techniques - Yutong Zong; Xiuling Yu; Minxiang Zhu; Shenggao Lu (Journal of Soils and Sediments, 2015)

Particle Margination and Its Implications on Intravenous Anticancer Drug Delivery - Erik Carboni; Katherine Tschudi; Jaewook Nam; Xiuling Lu; Anson W. K. Ma (AAPS PharmSciTech, 2014)

MicroRNA-21 promotes the proliferation and inhibits apoptosis in Eca109 via activating ERK1/2/MAPK pathway - Fengxia Liu; Shutao Zheng; Tao Liu; Qing Liu; Meng Liang; Xiuling Li; Ilyar Sheyhidin; Xiaomei Lu; Wenya Liu (Molecular and Cellular Biochemistry, 2013)

A solid-phase adsorption method for PEGylation of human serum albumin and staphylokinase: preparation, purification and biochemical characterization - Xiaoyan Suo; Xiuling Lu; Tao Hu; Guanghui Ma; Zhiguo Su (Biotechnology Letters, 2009)

Nanoparticles Containing Anti-inflammatory Agents as Chemotherapy Adjuvants II: Role of Plasma Esterases in Drug Release - Xiuling Lu; Melissa D. Howard; Dominique R. Talbert; John J. Rinehart; Philip M. Potter; Michael Jay; Markos Leggas (The AAPS Journal, 2009)

Nanoparticles Containing Anti-inflammatory Agents as Chemotherapy Adjuvants: Optimization and In Vitro Characterization - Xiuling Lu; Melissa D. Howard; Marta Mazik; Joshua Eldridge; John J. Rinehart; Michael Jay; Markos Leggas (The AAPS Journal, 2008)

A novel cross-linking reagent for bovine hemoglobin modification - Minglei He; Xiuling Lu; Dongxu Zhao; Zhiguo Su (Biotechnology Letters, 2003)